EPIDEMIOLOGY CHARACTERISTICS AND IMMUNIZATION STATUS OF DIPHTHERIA PATIENTS IN EAST JAVA PROVINCE IN 2018 - Dwi Rismayanti Wigrhadita (Universitas Airlangga, 2019)
Background: East Java Province is the region with the highest incidence of diphtheria in Indonesia. In the past three years, the number of diphtheria cases amounted to 758 cases and resulted in three mortalities. Objective: This study aims to describe the epidemiological characteristics and diphtheria immunization status of patients in East Java province in 2018. Methods: This study employed descriptive research with cross-sectional design. This study utilized secondary data of publication profiles from the East Java Provincial Health Office in 2018. The population was the entire diphtheria patients in East Java province, 2018. The samples were taken by using the total population sampling technique. The variables in this study were epidemiological characteristic and immunization status of diphtheria patients. The data analysis employed a univariate analysis by providing the frequency table. Results: Based on the records, diphtheria infected the children more often but, in 2018, it was also found in adults. This circumstance is proven by the findings that the patients were aged ≥19 years (33.11%) and were males (50.60%). In 2018, diphtheria patients number experienced an increase and decrease fluctuatingly as well as quite prevalence in some areas in the province of East Java. Diphtheria patients were predominanted by incomplete immunization status and unimmunized patients. Conclusion: The completeness status of diphtheria immunization has a very important role in the incidence of diphtheria cases in East Java Province in 2018, particularly the status of patients who is not complete and unimmunized.